2010
DOI: 10.1039/b921895e
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional cross-conjugated luminescent phosphines and phosphine derivatives: phospha-cruciforms

Abstract: Cross-conjugated bifunctional species including a phosphine, phosphine oxide, phosphine sulfide, phosphonium salt, phosphorus ylide and a gold(I) phosphine complex have been prepared. The photophysical characteristics of the series of compounds have been determined experimentally and are discussed/compared with simpler analogues lacking cross-conjugated branches and rationalized on the basis of DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…These attributes are ideal for ready polymer preparation and practical application of phosphonium polyelectrolytes. Furthermore, smallmolecule chromophore-modified phosphonium salts can have interesting photophysical properties such as high quantum efficiency, 31,33 and other organophosphorus materials have been used in electroluminescent devices. 34 We therefore became interested in polyelectrolytes featuring phosphonium salts as the charge-zbearing units in visible-absorbing and luminescent polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These attributes are ideal for ready polymer preparation and practical application of phosphonium polyelectrolytes. Furthermore, smallmolecule chromophore-modified phosphonium salts can have interesting photophysical properties such as high quantum efficiency, 31,33 and other organophosphorus materials have been used in electroluminescent devices. 34 We therefore became interested in polyelectrolytes featuring phosphonium salts as the charge-zbearing units in visible-absorbing and luminescent polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…We recently detailed the facile, modular synthesis of bifunctional visible-absorbing phosphines (VAPs) that are good candidates to serve as monomers for this approach. 33,35 Several derivatives and complexes of a VAP comprising a cross-conjugated platform (a phospha-cruciform) 33 and the application of a mesogen-spaced VAP (LHP1, Scheme 1) in the formation of luminescent Pt and Pd coordination polymers have also proven fruitful. 35 In the course of these studies, the examination of how photophysical properties can be tuned in various phosphorus(III) and phosphorus(V) derivatives of VAPs revealed that phosphonium salts can exhibit high photoluminescent quantum efficiencies relative to the other derivatives studied.…”
Section: Introductionmentioning
confidence: 99%
“… The absorption maximum of 1P is observed at 325 nm, but a weak absorption at around 400 nm (ε=260 cm −1 ·M −1 ) is also observed. The weak absorption is associated with the phosphorus‐based n‐π* transition . 1PO displays an absorption maximum at 342 nm, which is red‐shifted by 22 nm relative to that of BPEB because of the strong electron‐withdrawing P(=O) moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The weak absorption is associated with the phosphorus-based n-π* transition. [5] 1PO displays an absorption maximum at 342 nm, which is red-shifted by 22 nm relative to that of BPEB because of the strong electron-withdrawing P(=O) moiety. 1B shows an absorption maximum at 305 nm along with an absorption tail of 410 nm because of the p(B) π-π* conjugation of the dimesitylboryl group along the phenyleneethynylene framework.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Among them, functionalized cruciform‐shaped π‐conjugated compounds have attracted significant interest because of their excellent optoelectronic properties. These properties arise because of their unique, multiply conjugated pathway structures, which consist of two distinct molecular axes with either the same or different π‐conjugated arms 2. A common feature of this type of compound is that they have their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) geometrically separated.…”
Section: Introductionmentioning
confidence: 99%